SISTERHOOD IN ANN M. MARTIN'S BELLE TEAL - Delia Cesar Damayanti; Tri Pramesti (Anaphora : Journal of Language, Literary, and Cultural Studies, 2020)
A  relationship    called  sisterhood   has  become  an  ordinary   thing  in society.  The  sisterhood   docs  not only  happen  to fellow  women  without  blood  tics but  also  occur   between   relationships    across   generations    of  which   parents   and children  live.  To examine  the occurrence   of sisterhood  relationships   by parents  and children,  the writer  decided  to do a study  on a novel  entitled   Belle Teal by Ann M. Martin.  Using  qualitative  method,  the data  are analysed  descriptively.   By applying feminist   literary  criticism   the writer  discusses   several  problem   statements   which include   the  sisterhood   that  occurs  across   generations   and  how  sisterhood   can  be exposed  to cross-generational    relationships.   From  the analysis,   it can  be concludedthat  sisterhood   can  occur  across-generation.    Mutual   caring,  intimacy   and  shared activity   can  enhance   and  expose   sisterhood   relationship   among   the  perpetrators. Sisterhood   also  has a positive   impact  that  can  make  a person  have  a more  godly thought  than before.